Souls of contention and incommensurate mourning: commemorative rituals in contemporary China - Zhenru, Jacqueline Lin (Journal of contemporary religion, 2022)
This article examines commemorative rituals performed by local activists in the People’s Republic of China (PRC) for a group of forgotten soldiers who died in the Second World War. In a departure from the dichotomies found in current studies of ritualised remembrance between, for example, the state and the local, modern and traditional, and secular and religious, it probes how local communities incorporate the politicised rituals imposed by the Party state into their practices of mourning for the marginalised spiritual beings depicted in political propaganda. The data on these rituals, which were gathered in Hunan province where the largest number of bloody war battles occurred, are used to explore how the activists remember the war and venerate the fallen Kuomintang (KMT) soldiers. This article explores the ‘incommensurate mourning’ caused by the state’s political stigmatisation of the KMT during the Communist period and how the memorialisation of the war has been instrumentalised to promote nationalism in the state’s campaigns since the 2000s. In an attempt to reveal the injustice that the deceased faced and to revive the erased local history, Hunanese ‘redress activists’ organise public mourning rituals for two groups of war dead that are segregated by the degree of violence that caused their ‘second death’, which made it impossible to mourn the dead (Zhang 2013a). The first group are the Kuomintang soldiers whose graves were demolished, the second group are the unidentified soldiers who died in battle. Different posthumous afterlives of the perished soldiers engender distinct political and cultural barriers for the mourners. By foregrounding how the local activists incorporate the state’s soul-governing practices (Kipnis 2017, 2019) into their commemorative rituals, my analysis shows how these ritualised acts of remembrance challenge the Party’s monopoly of who counts as a ‘glorious soul’ in politicised acts of commemoration.